Reverting TP53 mutation in breast cancer cells: prime editing workflow and technical considerations - Abuhamad, Asmaa Y.; Mohamad Zamberi, Nurul Nadia; Sheen, Ling; Naes, Safaa M.; Mohd Yusuf, Siti Nur Hasanah; Ahmad Tajudin, Asilah; Mohtar, M. Aiman; Amir Hamzah, Amir Syahir; Syafruddin, Saiful Effendi (MDPI, 2022)
Breast cancer is the leading cause of cancer-related deaths in women. The aggressive breast cancer subtype is commonly linked to the genetic alterations in the TP53 tumor suppressor gene, predominantly the missense mutations. Robust experimental models are needed to gain better insights into these mutations’ molecular properties and implications in tumorigenesis. The generation of such models harboring the alterations is feasible with the CRISPR-based gene editing technology. Moreover, the development of new CRISPR applications, particularly DNA base and prime editing, has considerably improved the precision and versatility of gene editing. Here, we employed the prime editing tool to revert a TP53 missense C > T mutation (L194F) in a T47D luminal A breast cancer cell line. In parallel, this prime editing tool was also utilized to introduce the L194F mutation in HEK293T cells. To assess the prime editing efficiency in both cell lines, we first performed Sanger sequencing in the prime-edited cells pool and single cell-derived clones. However, the Sanger sequencing approach did not detect any base substitution in these cell lines. Next, by employing the more sensitive amplicon target sequencing, we managed to identify the expected substitution in these T47D and HEK293T cells, albeit the editing efficiency was low. In light of these findings, we discussed the technical aspects and provided suggestions for improve the prime editing workflow and efficiency for future experiments.